Digital television current state and perspective in Venezuela - Said, Elías (2008)
When a debate revolves around the digital transition of Latin America, it is a mayor challenge to establish a real period of time for its solidification. This emptiness and far away feeling isn’t different when boarding the subject in the Venezuelan reality, since there are almost no strategies for the development of a digital development in a communications oriented field, especially in the audiovisual field, were external factors can be considered in the same manner as the uniqueness and challenges of the country in this process, witch will clearly show how our countries works, waiting for the last moment to confront an even more tangible reality and with an even more variety of challenges that must be taken with seriousness and a glocal perspective.